THE EFFECT OF INDEPENDENCE RATIO, FISCAL DECENTRALIZATION DEGREE AND PAD EFFECTIVENESS ON HUMAN DEVELOPMENT INDEX THROUGH ECONOMIC GROWTH IN KARIMUN REGENCY - Ady Hermawan; Bambang Satriawan; Nolla Puspita Dewi (PT. Radja Intercontinental Publishing, 2024)
Human development is a development process that aims to enable humans to have more choices, especially in income, health and education where one of the benchmarks can be seen through the Human Development Index. This study aims to analyze and obtain empirical evidence on the effect of financial performance (independence level ratio, degree of fiscal decentralization, PAD effectiveness) and economic growth on the human development index in Karimun Regency. This study uses a quantitative method. The data used in this study are secondary time series data for 19 years and interviews. The data were analyzed using Structural Equation Modeling - Partial Last Square with the help of SMART PLS software version 3.0. The results of the study indicate that the independence level ratio has a positive and significant effect on the HDI. The degree of fiscal decentralization does not have a significant effect on the HDI. The effectiveness of PAD has a positive and significant effect on the HDI. Economic growth has a positive and significant effect on the HDI. The independence level ratio does not have a significant effect on economic growth. The degree of fiscal decentralization has a positive and significant effect on economic growth. The effectiveness of PAD does not have a significant effect on economic growth. The independence level ratio does not have a significant effect on the HDI through economic growth. The degree of fiscal decentralization has a positive and significant effect on the HDI through economic growth. The effectiveness of PAD does not have a significant effect on the HDI through economic growth. The HDI of Karimun Regency is influenced by the ratio of the level of independence, the degree of fiscal decentralization, the effectiveness of PAD and economic growth by 37.4%. While the economic growth of Karimun Regency is influenced by the ratio of the level of independence, the degree of fiscal decentralization and the effectiveness of PAD by 9.1%.